Metal phenolic aldehyde composite material with antibacterial synergistic effect and preparation method thereof

Through the nanosphere protocatechic acid-zinc composite synthesized under weak alkaline conditions, as a metal phenolic composite, the problems of poor heat resistance and easy drug resistance of existing antibacterial agents are solved, and the treatment of various bacteria is achieved. Effectively inhibit and broad-spectrum antibacterial effects, suitable for anticorrosion and medical supplies.

CN119143600APending Publication Date: 2024-12-17SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411291970.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing antibacterial agents have problems such as poor heat resistance, easy to produce drug resistance, high toxicity, small quantity and limited effects, and it is difficult to develop new antibacterial agents that are broad-spectrum, efficient and difficult to develop drug resistance.

Method used

Nanosphere procatechic acid-zinc composites synthesized by coordination reactions under weakly alkaline conditions are used as metal phenolic composite materials to prepare antibacterial agents. By controlling the reaction molar ratio and conditions, this composite material significantly improves its antibacterial properties against bacteria such as Escherichia coli, Yersinia enterocolitis and other bacteria.

Benefits of technology

It has achieved effective inhibition of pathogenic bacteria at low concentrations, significantly improved antibacterial performance, has broad-spectrum antibacterial effect, and is biocompatible. It is suitable for anticorrosion and medical supplies, and the preparation process is simple and can be expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a metal phenolic composite material with an antibacterial synergistic effect and a preparation method thereof, protocatechuic acid and zinc acetate are added according to a chemical reaction molar ratio, the protocatechuic acid and the zinc acetate can react under a weak alkaline condition through continuous heating and stirring, and a protocatechuic acid-zinc compound obtained through the reaction has an excellent broad-spectrum antibacterial effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial, and relates to a metal phenolic composite material and a preparation method thereof. Background Art

[0002] Bacterial and fungal infections pose a serious threat to human health. Traditional antimicrobial agents are generally divided into pharmaceutical antimicrobial agents, organic antimicrobial agents, natural antimicrobial agents, and inorganic antimicrobial agents. Pharmaceutical antimicrobial agents are mainly antibiotics, but the problem of antibiotic resistance is already very serious. The main varieties of organic antimicrobial agents are acylanilides, imidazoles, thiazoles, quaternary ammonium salts, and phenols. Although they have high antimicrobial efficiency and fast speed, they have poor heat resistance, are easy to hydrolyze, and are prone to drug resistance. Their safety remains to be studied. Inorganic antimicrobial agents are generally made by fixing metals such as silver, copper, and zinc (or their ions) on carriers such as zirconium phosphate, glass, zeolite, ceramics, and activated carbon through physical adsorption or ion exchange. Inorganic antimicrobial agents have certain toxicity, which often affects their antimicrobial effects. Natural antimicrobial agents are mainly extracted from natural plants, such as chitin, mustard, castor oil, and wasabi, but they are small in number, limited in effect, poor in heat resistance, low in bactericidal rate, and cannot be used for a wide spectrum and long term. Therefore, the development of new antimicrobial agents that are broad-spectrum, highly effective and less likely to develop drug resistance has become one of the current research hotspots.

[0003] Metal phenolic networks (MPNs) are an organic-inorganic hybrid network system developed in recent years. They utilize the coordination of phenolic ligands and metal ions to show excellent anti-inflammatory, antioxidant, antibacterial and other functional properties, and have low toxicity. In addition, MPNs can be produced and applied on a large scale due to their simple synthesis process, low production cost and high efficiency. For example, studies have shown that the polyphenol epigallocatechin gallate (EGCG), metal ions (Cu 2+) and the inoculant sodium diethyldithiocarbamate (DEDTC) were assembled in one step in aqueous solution to synthesize antimicrobial MPNs (am-MPN) nanoparticles, which can effectively inhibit MRSA and Escherichia coli, destroy biofilms, and promote wound healing in MRSA-infected mice (see: Yu R, ChenH, He J, et al. Engineering antimicrobial metal-phenolic network nanoparticles with high biocompatibility for wound healing. Advanced Materials, 2024, 36(6): 2307680, https: / / doi.org / 10.1002 / adma.202307680). Zinc, as a metal element that microorganisms rely on for survival and reproduction, can stabilize the folding conformation of metalloproteins and participate in important biochemical reactions. Zinc is closely related to a large number of metabolic and toxic pathways of microorganisms, and is particularly important in the process of microbial infection. Inhibiting the zinc ion transport system to affect the homeostasis of zinc ions will have an inhibitory effect on microbial contamination and infection. Protocatechuic acid (PCA) is a natural water-soluble organic compound widely distributed in vegetables, fruits, cereals and tea leaves. It also exists in a variety of Chinese medicinal materials, such as Salvia miltiorrhiza, Acanthopanax quinquefolius, Eucommia ulmoides, and Holly leaves. PCA has a wide range of biological activities, such as antioxidant, anti-inflammatory, antibacterial, antiviral, anti-aging, anticancer, anti-tumor and neuroprotective. Studies have shown that PCA has an inhibitory effect on both bacteria and fungi, but the antibacterial effect of PCA is moderate.

[0004] To date, there are some reports that PCA is used together with other substances (such as metal salts, antibiotics) (such as coordination reaction, combination) to inhibit or kill bacteria and other microorganisms, but the actual application effect is unclear (see: Chinese patent CN1410401A, etc.) or is not ideal (see: Study on the sensitization effect of active ingredients of traditional Chinese medicine on ESBLs-producing Escherichia coli. Journal of Jilin Agricultural Science and Technology College, 2023, 32(02): 5-9. etc.). Summary of the invention

[0005] The object of the present invention is to provide a metal phenolic composite material with antibacterial and synergistic effects and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, a metal phenolic composite material is provided, the composite material comprising a protocatechuic acid-zinc composite, wherein the protocatechuic acid-zinc composite adopts a protocatechuic acid:zinc ion coordination ratio of 1:0.5-2.

[0007] Preferably, the protocatechuic acid-zinc complex is a nano-spherical particle.

[0008] Preferably, the composite material is prepared by complexing protocatechuic acid and zinc ions through a coordination reaction.

[0009] The preparation method of the metal phenolic composite material comprises the following steps: Under weak alkaline conditions, protocatechuic acid and zinc acetate react in a solvent by continuous heating and stirring (in the reaction, zinc acetate dissociates to form acetate and zinc ions, and the zinc ions formed after the dissociation of zinc acetate combine with protocatechuic acid after the hydrogen ions are removed through coordination bonds, thereby generating a protocatechuic acid-zinc complex), and the chemical reaction molar ratio of protocatechuic acid to zinc acetate is 1:0.5-2; after the reaction is completed, the solids in the reaction system are separated and purified to obtain a metal phenolic composite material (i.e., protocatechuic acid-zinc composite material).

[0010] Preferably, the protocatechuic acid and zinc acetate are analytically pure.

[0011] Preferably, the weakly alkaline condition is obtained by using an alkaline reagent and adjusting the pH to 8.0-8.2 (the weakly alkaline environment can better dissociate zinc acetate in the reaction).

[0012] Preferably, the solvent of the reaction is deionized water.

[0013] Preferably, the initial concentration of protocatechuic acid in the solvent is 10-20 mM.

[0014] Preferably, the reaction temperature is 50-55° C. (more conducive to the forward reaction), the reaction time is 3-4 h, and the stirring speed during the reaction is 500-600 r / min.

[0015] Preferably, the separation specifically comprises the following steps: centrifuging the system after the reaction, then discarding the upper liquid, and retaining the precipitate (mainly containing nano-spherical protocatechuic acid-zinc complex).

[0016] Preferably, the purification specifically comprises the following steps: washing the precipitate containing the protocatechuic acid-zinc complex alternately with anhydrous ethanol and deionized water (to remove the incompletely reacted substances therein and increase the purity of the product), and after washing, vacuum drying at 45-55°C.

[0017] In a second aspect, an antibacterial agent is provided, comprising the metal phenolic composite material.

[0018] Preferably, the antibacterial spectrum of the antibacterial agent includes pathogenic bacteria such as Escherichia coli, Yersinia (such as Yersinia enterocolitica), Salmonella, Shigella (such as Shigella flexneri), Staphylococcus aureus, etc.

[0019] In a third aspect, the invention provides application of the metal phenolic composite material in preparing an antibacterial agent.

[0020] Preferably, the antibacterial agent further comprises a carrier and / or other compatible drugs.

[0021] Preferably, the carrier includes one or more of ceramics, zeolites and the like.

[0022] Preferably, the compatible drugs include one or more of acylanilides, imidazoles, thiazoles, isothiazolone derivatives, quaternary ammonium salts, bisguanidines, and antibiotics.

[0023] The beneficial effects of the present invention are embodied in: The metal phenolic composite material of the present invention is mainly composed of a protocatechuic acid-zinc complex with a certain coordination ratio. It is confirmed by co-culture with bacteria on a plate and spot plate experiments that a low concentration of the protocatechuic acid-zinc composite material has an inhibitory effect on pathogenic bacteria, and compared with the antibacterial activity of protocatechuic acid and zinc acetate, the antibacterial performance of the composite material on bacteria such as Escherichia coli, Yersinia enterocolitica, and Shigella flexneri is significantly improved, and the composite material can be used as an antibacterial agent.

[0024] The present invention can efficiently prepare a metal phenolic composite material with significant antibacterial effect by controlling the chemical reaction molar ratio of protocatechuic acid and zinc acetate during the reaction of the two raw materials and separating and purifying the solids in the system after the reaction. The reaction conditions are simple (such as heating and stirring in water), which is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a visual picture of the protocatechuic acid-zinc complex suspension obtained after the reaction.

[0026] Figure 2a This is a scanning electron microscope image of the material: from left to right: protocatechuic acid, zinc acetate, and protocatechuic acid-zinc composite material.

[0027] Figure 2b This is the EDS spectrum of the protocatechuic acid-zinc composite material: from left to right are C, O, Zn and element distribution (At%: C 53.8%; Zn 23.9%; O 22.3%).

[0028] Figure 3This is a plate diagram of the inhibition experiment of protocatechuic acid, zinc acetate, protocatechuic acid-zinc composite material, and protocatechuic acid and zinc acetate mixed solution on Escherichia coli CICC 25013 and Yersinia enterocolitica CICC 21669 (CK is the blank control group).

[0029] Figure 4 This is a plate diagram of the inhibition experiment of protocatechuic acid, zinc acetate, protocatechuic acid-zinc composite material, and protocatechuic acid and zinc acetate mixed solution on Shigella flexneri CICC 21534 (CK is the blank control group).

[0030] Figure 5 The dot plate diagram of the inhibition experiment of different protocatechuic acid-zinc composite materials on Salmonella Enteritidis CICC 21513 (CK is the blank control group; numbers 1 to 11 are gradient numbers): (A) protocatechuic acid-zinc composite material prepared with protocatechuic acid and zinc acetate as raw materials; (B) protocatechuic acid-zinc composite material prepared with protocatechuic acid and zinc sulfate as raw materials. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The embodiments are only used to explain the present invention, but not to limit the scope of protection of the present invention.

[0032] (I) Preparation and antibacterial activity of protocatechuic acid-zinc composite materials 1.1 Preparation experiment Experimental process: In a weakly alkaline reaction environment, deionized water is used as the reaction solvent. According to the chemical reaction molar ratio (the molar ratios of multiple substances are determined according to the possible chemical reaction formula, and experiments are carried out separately), the measured protocatechuic acid and zinc acetate are added, and the reaction system is continuously heated and stirred until the reaction is completed. The protocatechuic acid-zinc complex formed in the reaction system is separated and purified, and the purified complex is observed by electron microscopy. In the experiment, it was found that the selection of reaction conditions (in addition to the reaction solvent, it also includes the pH of the reaction environment, the chemical reaction molar ratio, the reaction temperature, the reaction time, etc.) has an important influence on the morphological structure (including particle size, etc.) of the obtained protocatechuic acid-zinc complex, especially on the antibacterial properties of the complex. In addition, the reaction raw materials used in the experiment, such as protocatechuic acid, zinc acetate, etc., are all analytically pure.

[0033] Preparation example of protocatechuic acid-zinc composite material: the reaction solvent used is deionized water, the reaction environment pH=8.2, the chemical reaction molar ratio is 1:1 (protocatechuic acid: zinc acetate), the reaction temperature is 50°C, and the reaction time is 4 h; the reaction is carried out in a reaction bottle (or serum bottle) with a certain volume capacity, after adding the reaction raw materials protocatechuic acid (12.98 mM) and zinc acetate (12.98 mM) to the reaction solvent, the reaction environment pH is adjusted with 1 mol / L NaOH solution, and after the pH is adjusted, it is heated to the reaction temperature, and stirred continuously at a speed of 550 r / min during the reaction. After the reaction was completed, heating and stirring were stopped, and the reaction system (in the form of a suspension) was centrifuged at 8000 r / min (room temperature) for 10 min to preliminarily separate the solids after the reaction. The separated solids were washed alternately with anhydrous ethanol and deionized water for 3 times, and centrifuged at 8000 r / min (room temperature) for 10 min after each washing. Finally, they were dried in a vacuum drying oven at 50°C to obtain solid powder.

[0034] Experimental results: Figure 1 The suspension shown in the figure is the reaction system after the protocatechuic acid-zinc composite is synthesized under the reaction conditions of the above example; the solid powder obtained after further separation and purification is sampled by electron microscopy, and the morphology of the protocatechuic acid-zinc composite material is observed by scanning electron microscopy. Figure 2a As shown in the figure, after protocatechuic acid and zinc acetate react under certain conditions, a composite material with a nanostructure is finally prepared (which is different from the scanning electron microscope images of the two single-component raw materials, protocatechuic acid and zinc acetate). A large number of spherical (or quasi-spherical) nanoparticles in the composite material are the synthesized protocatechuic acid-zinc complex; detected by EDS energy dispersive spectrometer; as shown in the figure Figure 2b As shown, the element composition of the protocatechuic acid-zinc composite material is C, O, and Zn, and they occupy a certain proportion. It can be seen that the obtained product is a zinc-containing complex, which verifies that the protocatechuic acid-zinc composite material is formed by the complex of protocatechuic acid and zinc ions.

[0035] 1.2 Antibacterial experiment Experimental principle: The mixed co-culture plate coating method was used to determine the antibacterial effect of protocatechuic acid-zinc composite materials (specifically synthetic protocatechuic acid-zinc complexes) by comparing the growth of Escherichia coli and Yersinia enterocolitica treated with protocatechuic acid, zinc acetate, a mixture of protocatechuic acid and zinc acetate, and protocatechuic acid-zinc composite materials.

[0036] Experimental procedure: Single colonies of Escherichia coli CICC 25013 and Yersinia enterocolitica CICC 21669 were selected and placed in LB and TSB liquid culture media, and cultured in a shaking incubator at 37°C for 12-18 h to activate the first-generation bacteria. 100 μL of the first-generation bacteria were inoculated into 30 mL LB and TSB liquid culture media, and cultured in a shaking incubator at 37°C until the bacterial solution concentration reached 1×10 8 CFU / mL, 1 mL of bacterial solution was taken into centrifuge tubes, centrifuged at 8000 r / min (room temperature) for 5 min to remove the culture medium, and the bacterial precipitate was washed twice with sterilized saline. Finally, the bacterial precipitate resuspended with 1 mL of protocatechuic acid-zinc composite material solution was used as the experimental group, and the bacterial precipitate resuspended with 1 mL of protocatechuic acid solution, zinc acetate solution, protocatechuic acid and zinc acetate mixed solution and saline was used as control group-1, control group-2, control group-3 and blank control group. After co-culture for 4 h (37°C shaker), 50 μL of the two bacterial solutions of each group were taken and applied to LB and TSB solid culture media respectively. The plates were inverted in a 37°C incubator for 10 h to observe the growth of the colonies.

[0037] The preparation of the above-mentioned drug solutions is as follows (the drug solution concentrations are shown in Table 1): use physiological saline to prepare protocatechuic acid solution, zinc acetate solution, mixed solution of protocatechuic acid and zinc acetate, and protocatechuic acid-zinc composite material suspension.

[0038] Table 1. Bacterial inhibition test of protocatechuic acid-zinc composite materials

[0039] Note: The drug solutions in Table 1 are all prepared with normal saline as solvent. "Protocatechuic acid", "zinc acetate" and "protocatechuic acid-zinc composite material" in Table 1 are the drug components of the corresponding groups of drug solutions. "-" means that the drug concentration is 0. "Protocatechuic acid-zinc composite material" specifically adopts the composite material prepared in the example in 1.1.

[0040] Experimental results: From Figure 3 It can be seen that for Escherichia coli and Yersinia enterocolitica, only the experimental group treated with protocatechuic acid-zinc composite material did not grow colonies, which was significantly different from the blank control group, while the control group treated with protocatechuic acid and zinc acetate alone was similar to the blank control group, with colonies growing. It can be seen that the protocatechuic acid-zinc composite material has good antibacterial properties and is significantly better than protocatechuic acid and zinc acetate. Figure 3 It can also be seen that the control group treated with the mixture of protocatechuic acid and zinc acetate still had colonies growing.

[0041] In addition, for pathogenic bacteria such as Shigella flexneri, the antibacterial properties of the protocatechuic acid solution, zinc acetate solution, mixed solution of protocatechuic acid and zinc acetate, and protocatechuic acid-zinc composite material suspension treated with the same concentration (0.81 mM) and the mixed co-culture plate coating method were as follows: Figure 4 shown.

[0042] Based on the results of the above experiments, it can be concluded that the composite material with a nanosphere structure (i.e., protocatechuic acid-zinc composite material) prepared by controlling the reaction conditions obtains the potential multi-target synergistic effect of protocatechuic acid and zinc acetate in antibacterial performance; to a certain extent, it shows that the synthesis of protocatechuic acid-zinc complex is beneficial to the improvement of antibacterial performance.

[0043] (II) Comparison of antibacterial activity with other protocatechuic acid-zinc composite materials 2.1 Preparation of other protocatechuic acid-zinc composites Referring to the preparation example of the composite material in (I), under the same weak alkaline reaction environment, deionized water was used as the reaction solvent, and other zinc-containing metal salts (specifically zinc sulfate) and protocatechuic acid (zinc sulfate: protocatechuic acid is 1:1) were added according to the chemical reaction molar ratio, and then heated and stirred for a certain period of time (reaction temperature was 50°C, reaction time was 4 h). After the reaction, the obtained protocatechuic acid-zinc complex suspension was further separated and purified (i.e., after centrifugation, it was washed alternately with anhydrous ethanol and deionized water for 4 times, and finally dried in a 50°C vacuum drying oven to form a solid powder), to obtain a composite material mainly composed of a protocatechuic acid-zinc complex (similar to the synthesis mechanism of the protocatechuic acid-zinc complex in 1.1, the difference is that SO4 2- It has strong adsorption capacity, and zinc sulfate is not easy to dissociate to form zinc ions, so its coordination effect with dehydrogenated protocatechuic acid is not as good as zinc acetate).

[0044] 2.2 Antibacterial experiment Experimental principle: The mixed co-culture spot plate method was used to obtain the antibacterial properties of the composite materials made of zinc sulfate and protocatechuic acid, and zinc acetate and protocatechuic acid, respectively, and to compare the antibacterial effects of different protocatechuic acid-zinc composite materials.

[0045] Experimental procedure: A single colony of Enteritidis Salmonella (strain number CICC 21513) was selected and placed in LB liquid medium. The culture was shaken at 37°C for 12-18 h to activate the first-generation bacteria. 100 μL of the first-generation bacteria was inoculated into 30 mL LB liquid medium and cultured at 37°C in a shaker until the bacterial solution concentration reached 1×10 8CFU / mL, 1 mL of bacterial solution was aspirated into a centrifuge tube, centrifuged at 8000r / min (room temperature) for 5 min to remove the culture medium, and the bacterial precipitate was washed twice with sterile saline, and finally the bacterial precipitate was resuspended with 1 mL of protocatechuic acid-zinc composite material solution of different concentrations prepared by protocatechuic acid and zinc acetate, and the bacterial precipitate was resuspended with 1 mL of protocatechuic acid-zinc composite material solution of the same concentration prepared by protocatechuic acid and zinc sulfate as a composite material control, and the bacterial precipitate was resuspended with 1 mL of saline as a blank control; after co-culture for 4 h (37°C shaker), 3 μL of the bacterial solution treated with different protocatechuic acid-zinc composite materials was aspirated and plated on LB solid culture medium (blank control was also plated), the plate was inverted in a 37°C incubator for culture for 10 h, and the growth of the colonies was observed.

[0046] The preparation of the above solutions is described as follows (the concentrations of the solutions are shown in Table 2): The solutions of the two protocatechuic acid-zinc composite materials are obtained by resuspending the powder in physiological saline.

[0047] Table 2. The gradient of the solution on the two composite materials

[0048] Note: The medicinal solutions in Table 2 are all prepared with physiological saline as solvent; "protocatechuic acid-zinc composite material prepared with protocatechuic acid and zinc acetate as raw materials" specifically adopts the composite material prepared in Example 1.1.

[0049] Experimental results: From Figure 5 It can be seen that the minimum inhibitory concentration of the protocatechuic acid-zinc composite material prepared by protocatechuic acid and zinc acetate for the inhibition of Salmonella enteritidis is about 0.2 mM ( Figure 5 A), the minimum inhibitory concentration of the protocatechuic acid-zinc composite material prepared by protocatechuic acid and zinc sulfate is about 0.81mM ( Figure 5 B), by comparison, it can be seen that the protocatechuic acid-zinc composite material prepared from protocatechuic acid and zinc acetate has a better antibacterial effect.

[0050] In summary, the present invention proposes a protocatechuic acid-zinc composite material prepared by protocatechuic acid and zinc acetate based on a certain coordination ratio. Compared with traditional single metal salts or metal antibacterial agents, it not only has the advantage of good biocompatibility due to the presence of natural plant-derived substances, but also has excellent broad-spectrum antibacterial effects, and has wide application potential in related fields such as antiseptic and antibacterial of medical supplies (such as instruments). At the same time, the present invention proposes a composite material preparation method for synthesizing a protocatechuic acid-zinc complex by reacting protocatechuic acid and zinc acetate under weakly alkaline conditions, which has the advantages of simple preparation process, high repeatability, and high yield, and is easy to scale up production.

Claims

1. A metal phenolic composite material, characterized in that: The composite material comprises a protocatechuic acid-zinc complex, wherein the protocatechuic acid-zinc complex adopts a protocatechuic acid:zinc ion coordination ratio of 1:0.5-2.

2. The metal phenolic composite material according to claim 1, characterized in that: The protocatechuic acid-zinc complex is a nano spherical particle.

3. The metal phenolic composite material according to claim 1, characterized in that: The composite material is prepared by compounding protocatechuic acid and zinc ions through coordination reaction.

4. A method for preparing a metal phenolic composite material, characterized in that: The following steps are involved: Protocatechuic acid and zinc acetate are reacted in a solvent, and zinc ions formed by the dissociation of zinc acetate in the reaction are combined with protocatechuic acid after the hydrogen ions are removed through coordination bonds, and the molar ratio of the protocatechuic acid to the zinc acetate is 1:0.5-2; after the reaction is completed, the solid matter in the reaction system is separated and purified to obtain a metal phenolic composite material.

5. The method for preparing a metal phenolic composite material according to claim 4, characterized in that: The reaction is carried out under weakly alkaline conditions of pH 8.0-8.

2.

6. The method for preparing a metal phenolic composite material according to claim 4, characterized in that: The solvent is water.

7. The method for preparing a metal phenolic composite material according to claim 4, characterized in that: The initial concentration of protocatechuic acid in the solvent is 10-20 mM.

8. The method for preparing a metal phenolic composite material according to claim 4, characterized in that: The reaction temperature is 50-55° C., the reaction time is 3-4 h, and the stirring speed during the reaction is 500-600 r / min.

9. An antibacterial agent, characterized in that: It comprises the metal phenolic composite material as described in any one of claims 1 to 3.

10. Use of the metal phenolic composite material according to any one of claims 1 to 3 in the preparation of an antibacterial agent.